Human Rights and the Price of Upward Mobilityin Dur-e-Aziz Amna’s A Splintering (Journal of Asian Development Studies, 2026)
This thesis examines how the pursuit of human rights and upward mobility leads to tragedyrather than fulfilment for a subaltern woman in Dur e Aziz Amna’s A Splintering (2025). Itfocuses on Tara, a young woman from a poor family in rural Punjab, Pakistan. This studyapplies Ratna Kapur’s human rights critique to explain how Tara’s ambition shifts fromaspirational to avaricious and how she becomes what Kapur calls a “failed or unhappysubaltern subject.” The concept of the “failed or unhappy subaltern subject” has been studiedin human rights scholarship, but this investigation applies it specifically to a contemporaryPakistani novel, thereby filling a significant gap in the literature. The analysis, which isqualitative in nature, applies Kapur’s theoretical framework to argue that the acquisition ofhuman rights represents the “terminal limits” of what rights can achieve rather than themoment of liberation. The main argument is that Tara’s upward mobility does not lead tofreedom and happiness but instead to despair and moral corruption. Human rights, as Kapurargues, cannot produce meaningful happiness for subaltern subjects